The effect of gender on the story-writing style of the novels My Bird, From Satan Learnt and Burnt, Your Redness from Me, and Bibi Shahrazad based on Sara Mills’s Theory - Fatemeh Ranjbar; Hassan Akbari Beyragh (مطالعات زبانی و بلاغی)
Feminist stylistics is a new approach that focuses on novels published by women and on the production, reproduction and transformations of style, gender identities and power relations between women and men. The current research has selected four novels from the 1980s; the titles My Bird (Parande Man) (2008), From Satan Learnt and Burnt (Az Sheitān Āmūkht va Sūzāand) (2008), Sorkhi to az Man (Your Redness from Me) (2008) by Bibi Shahrzad (2009). Using the descriptive-analytical method and based on Sara Mills' feminist stylistic model, the study examines these texts at three levels; lexical, sentence and discourse. The results of the research show that at word level in all the investigated novels, feminine interpretations and words related to the position of women such as pregnancy, love, virginity, childbirth, nausea, rape, abortion, cosmetics, etc. have been widely used. These words show the female identity of the authors of the stories from the individual-gender, ideological, class dimension and women's attention to the home environment and society. At the level of sentences (syntax), short, simple, detailed statements, the emotional dimensions of the text and the omission of the verb in sentences as well as interrupted sentences were consecutively examined in all the four novels. At this level, the use of short, repetitive and descriptive detailed statements without literary and rhetorical complications have a high frequency in all four works. At the discourse level, all the works, while dealing with gender stereotypes in the society, try to challenge the male culture and the long history of patriarchy. Thematically, all the four novels revolve around women's lives and are related to the issues, problems and oppressions that women face in society and family. The main characters of all the novels are women. Men are on the sidelines and are not allowed to speak much. The relationship between men and women is disjointed, chaotic and suffering from serious crises. Therefore, it can be said that the novels discussed in this research have all followed the model proposed by Sara Mills, and the characteristics and features of women's writing can often be found in these texts. As a result, it seems that, although a literary work is a product of an artist's mentality, language and world, the structural differences of gender are effective in creating linguistic, mental, stylistic and thought differences.